Child Abuse: Should we have conscious awareness? A study to assess cognizance of dentists concerning child abuse in Ludhiana City - Nishita Rana; Namita Singh; Shaila Shamsher; Abi M Thomas (CHRISMED Journal of Health and Research, 2022)
Introduction: Child abuse is an increasing social problem with serious lifetime impact. Almost half of the violence cases affect the head-and-neck region, so dentists can play a proactive role in identifying and reporting possible cases of child abuse. Aim: This study aims to assess the knowledge and attitude about physical and social indicators, legal aspects, and barriers in reporting mechanisms toward child abuse among dentists in Ludhiana city. Methodology: With prior consent, a self-administered structured questionnaire comprising 21 questions was distributed to 100 state-registered dentists of Ludhiana city. The data collected were descriptively analyzed using Pearson Chi-square test. Results: A total of 92 dentists responded to the questionnaire, with a response rate of 92%. Among them, 43% were females, while males were 57% and 64.4% of dentists were specialists, out of which 21% were pedodontists. A moderate proportion of the dentists (68%) had knowledge about indicators. The knowledge of indicators was more among pedodontists. However, no significant difference was seen between other respondents and pedodontists. Almost 79% knew their legal duty to report the suspected case. Forty percent of the dentist had encountered with child abuse cases with a significant difference among pedodontists when compared to other respondents, but only 23% reported a case. Fear of litigation, lack of referral knowledge, and uncertainty of diagnosis were major barriers in reporting. Ninety-two percent showed a positive attitude for further training in identification and reporting mechanisms for suspected cases. Conclusion: The respondent dentists had moderate knowledge regarding child abuse, positive attitude toward dealing with child abuse, but they were diffident and unaware of the appropriate authority to report. Considering this fact, a systematic educational program in diagnosis and reporting of child abuse is advised to provide adequate knowledge than lecture-based learning.